Perceptions of Social Studies Teachers Regarding Savings Value - Çakmak, Zafer; Yi?Ğen, Veysel (The International Society for Technology Education and Science, 2020)
The use of human beings with the thought that their scarce resources will never end, reminds us of the necessity of saving value to us and all the citizens of the world. We can define saving as using the available resources sparingly and sparingly. Saving the saving value at an early age in individuals will have an impact on the thoughts and behaviors of individuals who will assume responsibilities in the future society. For this reason, it is essential that we gain this value, which we will feel in every aspect of life, in the family and then in schools. Education and training activities aim to provide students with academic knowledge as well as gain value and skills. The 2018 Social Studies Curriculum includes 18 values that should be gained to students and one of these values is the “savings” value. The program has goals such as individuals to show sensitivity to the issues that concern their country and the world, to protect their natural environment, to realize that resources are limited and act consciously. Given these goals, the function of the Social Studies course to raise individuals in social life is important. This function can be presented to students effectively and efficiently through social studies lesson activities in schools. Qualitative research model was used in this study. The data were analyzed with Nvivo 2011 program. As a result of the study, different perceptions of Social Studies teachers were reached. Various suggestions are presented in line with the obtained results. © 2020 Published by ISRES Publishing
Sosyal Bilgiler Öğretmenlerinin Tasarruf Değerine İlişkin Algıları
International Conference on Research in Education and Science, ICRES 2020 -- 21 March 2020 through 24 March 2020 -- Istanbul -- 187303
Keywords: Education; Savings; Social studies teacher; Training